IMPROVING STUDENTS’ CREATIVE ABILITIES THROUGH TEACHING ART LESSONS USING INFORMATION AND COMMUNICATION TECHNOLOGIES - Abduxamidov Quvonchbek Yangiboy o‘g‘li (Web of Journals Publishing, 2024)
This article discusses how ensuring the implementation of modern information technologies in the field of education with advanced modern information and communication technologies fundamentally changes the content and essence of education for students and is one of the important aspects of applying modern information technologies.
Keywords: Virtual, animated, communication, personal computer, monoblock, server, reproduction, tablet, interactive, platform, method, heuristic.